Potential of Aquatic Plant as Phytoremediator for Treatment of Petrochemical Wastewater in Gebeng Area, Kuantan - Abdul Syukor, Abd Razak; Zularisam, A. W.; Ideris, Zakaria; Mohd. Ismid, Mohd. Said; Suryati, Sulaiman; Hasmanie, Abdul Halim; Diana Laura, Thomas (AENSI, 2013)
Malaysia is a vast developing country that partly relies on its oil and gas sector industries for economic growth. However, rapid industrialization has resulted in production of massive amount of wastewater daily that may contain heavy metals and other contaminants. Phytoremediation is a promising technology and reliable method that uses plants to degrade, assimilate, metabolize, or detoxify contaminant. The objectives of this study are to identify the potential of aquatic plant and the percentage of contaminant removal in treating Petrochemical wastewater via phytoremediation. Three aquatic plants were use in this study; Eichhornia crasspies sp., Pistia statiotes sp. and Landoltai punctata sp. Sampling method was carried out once for every 3 days and continues for 7 weeks period. Overall, 12 parameters are used to measure the effectiveness of phytoremediation process which are; BOD, COD, DO, pH, Turbidity, Cadmium, Zinc, Iron, Cooper, Lead, Nitrate and Chromium. Analysis of data was performed by using 1-way ANOVA.